Water quality, biomass and extracellular polymeric substances in an integrated algae pond system - Jimoh, Taobat Adekilekun (Rhodes University, Faculty of Science, Institute for Environmental Biotechnology, 2018)
Integrated algae pond systems (IAPS) combine the use of anaerobic and aerobic bioprocesses to effect wastewater treatment. Although, IAPS as a technology process offers many advantages including efficient and simultaneous N and P removal, no requirement for additional chemicals, O2 generation, CO2 mitigation, and a biomass with potential for valorization, a lack of technological advancement and the need for large land area, has limited the reach of this technology at industrial scale. In mitigation, peroxonation was introduced as a tertiary treatment unit and its effect on COD and TSS of IAPS treated water investigated. An effort was made to characterize the soluble but persistent COD in IAPS treated water and, productivity of the HRAOP mixed liquor was investigated to gain insight into the potential use of this biomass. Results show that peroxone treatment effectively reduced COD, TSS, and nutrient load of IAPS water without any significant impact on land area requirement. Indeed, summary data describing the effect of peroxone on quality of IAPS-treated water confirmed that it complies with the general limit values for either irrigation or discharge into a water resource that is not a listed water resource for volumes up to 2 ML of treated wastewater on any given day. Extraction followed by FT-IR spectroscopy was used to confirm albeit tentatively, the identity of the soluble but persistent COD in IAPS treated water as MaB-floc EPS. Results show that MaB-flocs from HRAOPs are assemblages of microorganisms produced as discrete aggregates as a result of microbial EPS production. A relationship between photosynthesis and EPS production was established by quantification of the EPS following exposure of MaB-flocs to either continuous light or darkness. Several novel strains of bacteria were isolated from HRAOP mixed liquor and 16S ribosomal genomic sequence analysis resulted in the molecular characterization of Planococcus maitriensis strain ECCN 45b. This is the first report of Planococcus maitriensis from a wastewater treatment process. Productivity and change in MaB-flocs concentration, measured as mixed liquor suspended solids (MLSS) between morning and evening were monitored and revealed that MLSS is composed of microalgae and bacteria but not fungi. Concentration varied from 77 mg L-1 in September (winter) to 285 mg L-1 in November (spring); pond productivity increased from 5.8 g m-2 d-1 (winter) to 21.5 g m-2 d-1 (spring); and, irrespective of MLSS concentration in late afternoon, approximately 39% was lost overnight, which presumably occurred due to passive removal by the algae settling pond. The outcomes of this research are discussed in terms of the quality of treated water, and the further development of IAPS as a platform technology for establishing a biorefinery within the wastewater treatment sector.
Keywords: Water -- Purification; Sewage -- Purification -- Anaerobic treatment; Sewage lagoons; Sewage disposal plants; ASPAM model (Acid mine drainage); Integrated algae pond systems (IAPS)